Multifunctional Indomethacin Conjugates for the Development of Nanosystems Targeting Cancer Treatment - Thiruchenthooran V; Świtalska M; Maciejewska G; Palko-Łabuz A; Bonilla-Vidal L; Wietrzyk J; Souto EB; Sánchez-López E; Gliszczyńska A (International Journal of Nanomedicine)
Vaikunthavasan Thiruchenthooran,1 Marta Świtalska,2 Gabriela Maciejewska,3,4 Anna Palko-Łabuz,5 Lorena Bonilla-Vidal,6,7 Joanna Wietrzyk,2 Eliana B Souto,8 Elena Sánchez-López,6,7,* Anna Gliszczyńska1,* 1Department of Food Chemistry and Biocatalysis, Wrocław University of Environmental and Life Sciences, Wrocław, Poland; 2Department of Experimental Oncology, Ludwik Hirszfeld Institute of Immunology and Experimental Therapy, Polish Academy of Sciences, Wrocław, Poland; 3Central Laboratory of the Instrumental Analysis, Wrocław University of Technology, Wrocław, Poland; 4Omics Research Center, Wrocław Medical University, Wrocław, Poland; 5Department of Biophysics and Neuroscience, Wrocław Medical University, Wrocław, Poland; 6Department of Pharmacy, Pharmaceutical Technology and Physical Chemistry, University of Barcelona, Barcelona, 08028, Spain; 7Institute of Nanoscience and Nanotechnology (IN2UB), University of Barcelona, Barcelona, 08028, Spain; 8UCD School of Chemical and Bioprocess Engineering, University College Dublin, Dublin, D04 V1W8, Ireland*These authors contributed equally to this workCorrespondence: Anna Gliszczyńska; Elena Sánchez-López, Email anna.gliszczynska@upwr.edu.pl; esanchezlopez@ub.eduPurpose: It is well known that the nonsteroidal anti-inflammatory drug (NSAID) indomethacin (IND) exhibits significant anticancer potential reported not only by in vitro and in vivo studies, but also in clinical trials. Despite promising results, IND is not widely used as an adjunctive agent in cancer therapy due to the occurrence of several gastrointestinal side effects, primarily after oral administration. Therefore, this study aimed to develop a nanosystem with reduced toxicity and risk of side effects for the delivery of IND for cancer treatment.Methods: IND was encapsulated in nanostructured lipid carriers (NLC) in the form of a phospholipid conjugate, where a covalent bond exists between the drug and phosphatidylcholine skeleton. For this purpose, seven new hybrid molecules were synthesized, and subsequently evaluated as anticancer agents in an in vitro model against selected cancer cell lines.Results: Biological studies demonstrated that the synthesized conjugates possessed excellent antiproliferative effects, exhibiting a 2.7-fold to even 100-fold higher activity against selected cancer cells, while remaining non-toxic to healthy cells. Based on biological studies and molecular calculations, heterosubstituted phosphatidylcholine containing IND and oleic acid (IND-OA-PC) in the sn-1 and sn-2 positions, respectively, was identified as the most potent molecule. Subsequently, IND-OA-PC was encapsulated in nanostructured lipid carriers (IND-OA-PC-NLC). The results revealed that IND-OA-PC-NLC has a spherical shape with an average diameter of 155 nm and a negatively charged surface (– 17.4 ± 0.49 mV). In this study, it was proven that the encapsulated conjugate of indomethacin with PC exhibits high activity against triple-negative (TNBC, Her2-, PR-, and ER-) breast cancer cells MDA-MB-468. While free IND was active at a concentration of 270.5 μM, in the form of the phospholipid conjugate (IND-OA-PC), it inhibited the growth of cancer cells at 67.5 μM and after conjugate encapsulation (IND-OA-PC-NLC) it was effective at only 10.3 μM.Conclusion: Our study revealed that the conjugation of NSAID with phosphatidylcholine and its combination with nanotechnology techniques create opportunities to repurpose well-known drugs from this group for new therapeutic applications.Keywords: indomethacin, phospholipid conjugates, long-chain fatty acids, nanostructured lipid carrier, nanoparticles, anticancer properties